DEVELOPMENT OF TACIT KNOWLEDGE IN LEAN MANAGEMENT IN AN ORGANIZATION: THE CASE OF AUTOMOTIVE INDUSTRY IN MALAYSIA (Journal of Technology and Operations Management, 2017)
Nowadays, the implementation of lean management has been on the rise globally especially in the automotive industry. However, there are several organizations still fail to apply lean management effectively and continuously. Each failure can be attributed in two different causes, which are lack of understanding of the concept of waste, and the fundamental issues of lean culture. To be successful in the implementation of lean management may not be easy. In order to create the foundation for lean to take hold, a significant organizational change must occur within the organization. The organization must fully understand the knowledge of lean management system and the lean management tools as well. Therefore, the purpose of this paper is to investigate development of tacit knowledge during the lean implementation. This study applied a qualitative method. A single case study was conducted in a Malaysian based automotive company. Based on the interview and observation conducted, the sources of development of tacit knowledge in lean management were developed from the training, database sharing, factory visit, previous case studies and internet (video) resources. Therefore, lean tacit knowledge is essential to the development of a successful organization.